1986
DOI: 10.1177/34.6.2871071
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody against tyrosine hydroxylase: application in light and electron microscopy.

Abstract: The catecholaminergic neurons of the nervous system have been studied histochemically with fluorescent derivatives of catecholamines and immunocytochemically using antibodies against their biosynthetic enzymes. The immunocytochemical techniques yield permanent preparations and make possible ultrastructural studies and combined applications with other procedures. In this report, we describe the production and application of a high-affinity mouse monoclonal antibody against the rate-limiting enzyme in I Supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…In order to detect the TH immunoreactive (C) cell bodies, their immediate processes in the arcuate nucleus and distal axons in the median eminence free-floating sections were subjected to immunocytochemistry for TH as described by Ezquer & Seltzer (2003) using mouse monoclonal antibody against TH (Semenenko et al 1986) diluted in the ratio of 1:50 in carrier solution and revealed with avidin-biotin-peroxidase (ABC Kit, Vector Corporation) diluted to 1:100 in Tris buffer (TB, 0.1 M Tris-HCl (pH 7.4)). In the control specificity experiments, the primary antibody was omitted in the course of immunostaining.…”
Section: Th Ihcmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to detect the TH immunoreactive (C) cell bodies, their immediate processes in the arcuate nucleus and distal axons in the median eminence free-floating sections were subjected to immunocytochemistry for TH as described by Ezquer & Seltzer (2003) using mouse monoclonal antibody against TH (Semenenko et al 1986) diluted in the ratio of 1:50 in carrier solution and revealed with avidin-biotin-peroxidase (ABC Kit, Vector Corporation) diluted to 1:100 in Tris buffer (TB, 0.1 M Tris-HCl (pH 7.4)). In the control specificity experiments, the primary antibody was omitted in the course of immunostaining.…”
Section: Th Ihcmentioning
confidence: 99%
“…The samples were run, transferred to nitrocellulose membranes (Hybond C Amershan Life Science), and blotted for TH immunoreactivity as described by Ezquer & Seltzer (2003) using the primary antibody anti-TH (Semenenko et al 1986), at 1:500 dilution and revealed with horseradish peroxidase-conjugated goat anti-mouse (DAKO Corporation, Carpinteria, CA, USA) and detection by chemiluminescence (ECL TM, Amersham Pharmacia Biotech). Multiple exposures of different times were made, to bring the exposures within the linear response range of the film (X-OMAT-AR, Kodak) and quantified by densitometry using digital image processing and the freeware program NIH Image 1.6/ppc (developed at the US National Institutes of Health and available on the internet at http://rsb.info.nih.gov/nih-image/).…”
Section: Th Western Blotsmentioning
confidence: 99%
“…The samples were analyzed for the presence of TH protein after separation by 12% SDS-PAGE on minigels in parallel with prestained protein molecular weight standards as described by Laemmli [35] loading 8 µg of cytoplasmatic proteins from each homogenate per lane. The samples were run, transferred to nitrocellulose membranes (Hybond C, Amershan Life Science) and blotted for TH immunoreactivity [29] using primary antibody anti-TH [34] at 1:500 dilution and revealed with horseradish peroxidase-conjugated goat anti-mouse (Dako Corp., Carpinteria, Calif., USA) and detection by chemiluminescence (ECL TM, Amersham Pharmacia Biotech, UK). Multiple exposures of different times were made, to bring the exposures within the linear response range of the film (X-OMAT-AR, Kodak) and quantified by densitometry using digital image processing and the freeware program NIH Image 1.6/ppc (developed at the US National Institutes of Health and available on the Internet at htpp://rsb.info.nih.gov/nih-image/).…”
Section: Methodsmentioning
confidence: 99%
“…In order to detect the TH-immunoreactive (+) cell bodies, their immediate processes in the arcuate nucleus and distal axons in the median eminence free-floating sections were subjected to immunocytochemistry for TH [29] using mouse monoclonal antibody against TH [34] diluted 1:50 in carrier solution and revealed with avidin biotin peroxidase diluted to 1:100 in Tris buffer (TB, 0.1 M Tris-HCl, pH 7.4) (ABC Kit, Vector Corp.). In the control specificity experiments the primary antibody was omitted in the course of immunostaining.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore all catecholamine-producing neurones express tyrosine hydroxylase. Monoclonal antibodies against this enzyme have also been produced by Semenenko et al [6], Ross et al [7] and more recently by Rohrer et al [8], who used a monoclonal antibody reacting with tyrosine hydroxylase present in homogenates of quail, chicken, rat and bovine adrenal gland. Several laboratories have purified tyrosine hydroxylase and produced polyclonal antibodies, which have been used in immunohistochemical [2], immunotitration [3] and neuroenibryological [4] experiments as well as for the localization of tyrosine-hydroxylase-producing neurones in brain and chromaffin cells of adrenal glands [5].…”
mentioning
confidence: 99%